2016
DOI: 10.3109/14756366.2016.1158171
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of antimicrobial, anticoagulant, and anticholinesterase hybrid molecules from 4-methylumbelliferone

Abstract: We designed and synthesized new series of diverse triazoles, isoxazoles, isoxazolines, and aziridines linked 4-methylumbelliferone 1 using intermolecular 1,3-dipolar cycloaddition reactions. Structures of these compounds were established on the basis of 1 H NMR, 13 C NMR, and ESI-HRMS. All prepared compounds were evaluated for their antimicrobial, anticoagulant, and anticholinesterase activities. Interestingly, among the tested molecules, some of the analogs displayed better activities than the parent 4-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The coumarin–1,2,3‐triazole conjugates 4 (Fig. ) exhibited significant in vitro antibacterial activity , while further incorporation of a chalcone moiety (hybrids 5 ) showed potential activity . The SAR revealed that the activity was affected greatly by the substituents on the chalcone moiety, and the contribution order of substituents on the activity was 4‐OMe > 4‐F > 4‐Cl > 4‐NMe 2 > 4‐ i ‐Pr > 4‐Me > ‐H; the number of ‐OMe on the chalcone moiety also influenced the activity greatly as evidenced by 3,4,5‐triOMe > 2,4‐diOMe > 4‐OMe.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 99%
“…The coumarin–1,2,3‐triazole conjugates 4 (Fig. ) exhibited significant in vitro antibacterial activity , while further incorporation of a chalcone moiety (hybrids 5 ) showed potential activity . The SAR revealed that the activity was affected greatly by the substituents on the chalcone moiety, and the contribution order of substituents on the activity was 4‐OMe > 4‐F > 4‐Cl > 4‐NMe 2 > 4‐ i ‐Pr > 4‐Me > ‐H; the number of ‐OMe on the chalcone moiety also influenced the activity greatly as evidenced by 3,4,5‐triOMe > 2,4‐diOMe > 4‐OMe.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 99%
“…Coumarin motifs containing triazole, isoxazoles, isoxazolines, and aziridines were synthesized by Zayane’s team using 1,3-DP cycloaddition reactions. Synthesis of isoxazolines via 1,3-DP cycloaddition of in situ-generated RCNO to allyloxycumarin is presented below— Scheme 112 [ 120 ].…”
Section: Syntheses Of Substituted 2-isoxazolines Via 13-dp Cycloaddit...mentioning
confidence: 99%
“… Syntheses of 3,5-disubstituted 2-isoxazolines equipped with the coumarin motif attached to the scaffold through CH 2 O linker [ 120 ]. Ar = Ph and XC 6 H 4 (X = MeO, O 2 N, Et, Cl); a = PhMe, Et 3 N; up to 58% yield.…”
Section: Figures and Schemesmentioning
confidence: 99%
“…Morpholinylmethyl- and piperazinylmethyl (N-R 1 ,R 2 )-containing hybrids exhibited noticeable activity against various bacterial pathogens and were more potent than the hybrids incorporating a phthalimidomethyl moiety in the 4 position of the triazole ring. The 6,8-disubstituted coumarin-1,2,3-triazole conjugates B (Figure 1) exhibited significant in vitro antibacterial activity [8,9]. Investigation of the antimicrobial activity of this type of hybrid compounds led to the identification of several different structural frameworks.…”
Section: Introductionmentioning
confidence: 99%